Relationship Between Gratitude With Well-Being Teens whose Parents Divorced - Yohanna Tungga Prameswarawati (International Consortium of Education and Culture Research Studies, 2020)
Gratitude and psychological well-being are aspects of positive emotions that exist in individuals. Individuals who have a sense of gratitude for being able to realize that he received a lot of goodness, good appreciation from God, others and the surrounding environment. While individuals who have psychological well-being when they are able to accept themselves, form warm relationships, have independence, control the external environment, have meaning in life and realize their potential continuously. The family is the smallest unit in society consisting of father, mother and child. The family can be the base of one's life, a source of care with affection, the first, most important and closest educational park that can be enjoyed because the teachings about the values ​​of life, both religious and socio-cultural are fundamental things that can be obtained in a family.The purpose of this study is to determine whether there is a relationship between gratitude and psychological well-being in adolescent boys and girls and who experience parental divorce.Research methods The subjects of this study were adolescents aged 15 to 20 years in two different cities. The sampling technique used is the cluster sampling method. Cluster sampling is sampling based on area or cluster. Clusters referred to in this study are classes in the school. Research subjects numbered 224 people. Whereas in other studies using a sampling technique used is sampling saturation. Samples that will be used in this study are as many populations as there are 33 students who have divorced parents, 20 students in class XI and 13 students in class XII. Data analysis using descriptive statistics with percentage techniques. Before calculating the percentage, a score group is made. Calculation of psychological well-being data for students whose parents are divorced is obtained based on the calculation of the average score (mean). The data generated in this study are descriptive percentage statistical techniques because the research describes the psychological well-being (psychological well-being) of students whose parents are divorced. 33 students.